Aging Genome Modification and Editing using the Crispr-Cas9 system: Anti-Alzheimer Study by Docking Methods - (:unkn) unknown (AMG Transcend Association, 2022)
Cas-9 is an enzyme that uses CRISPR sequences as a guide for detecting and separating a part of the genome which are complementary to the CRISPR sequence. Cas9 (CRISPR-associated protein 9, formerly called Cas5, Csn1, or Csx12) plays an important role in the human immune system against DNA viruses and is also utilized in genetic engineering approaches. They are able to cut a part of the DNA sequence in genome editing. CRISPR-Cas-9 editing was established by Emmanuelle Charpentier and Jennifer Doudna (Nobel Prize in Chemistry in 2020). CRISPR has been edited for making transcription items that permit researchers to activate specific genes. There are two categories of CRISPR-Cas; category 1 consists of multiple Cas proteins for degrading foreign nucleic bases. Category 2 consists of a single huge Cas protein for the same role. Aging results from a lifetime of stochastic destruction of tissues and cellular ingredients. Increasing age parallel causes a decrease of immunity and any inflammation related to reflecting incidents of cellular and tissue damage as a function of a lifetime. The DNA sensing signaling is activated via wrong placed cytosolic, which initiates the innate immune responses. Micronuclei are completely related to aging and affect aging due to always occurring in several aging syndromes and cancer. Therefore, micronuclei may present a mechanistic link among genome instabilities, innate immune activation, and a few hallmarks of aging tissues with the different drug properties of Verubecestat, Donepezil, Memantine, galantamine, Tacrine, Exelon, Rivastigmine, 7-MEOTA, and Acyclovir. Among them, Tacrine was found to have the highest (negative) binding energy and was further subjected to molecular dynamics (MD) simulation analysis.
Keywords: 3. Good health